Simulation framework for multigigabit applications at 60 GHz - Pires, Pedro Alexandre Seabra (2017)
This dissertation describes the implementation of a OFDM-based simulation framework for multigigabit applications at 60 GHz band over indoor multipath fading channels. The main goal of the framework is to provide a modular simulation tool designed for high data rate application in order to be easily adapted to a speci c standard or technology, such as 5G. The performance of OFDM using mmWave signals is severely a ected by non-linearities of the RF front-ends. This work analyses the impact of RF impairments in an OFDM system over multipath fading channels at 60 GHz using the proposed simulation framework. The impact of those impairments is evaluated through the metrics of BER, CFR, operation range and PSNR for residential and kiosk scenarios, suggested by the standard for LOS and NLOS. The presented framework allows the employment of 16 QAM or 64 QAM modulation scheme, and the length of the cyclic pre x extension is also con gurable. In order to simulate a realistic multipath fading channel, the proposed framework allows the insertion of a channel impulse response de ned by the user. The channel estimation can be performed either using pilot subcarriers or Golay sequence as channel estimation sequences. Independently of the channel estimation technique selected, frequency domain equalization is available through ZF approach or MMSE. The simulation framework also allows channel coding techniques in order to provide a more robustness transmission and to improve the link budget.